2017
DOI: 10.1161/cir.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

Meal Timing and Frequency: Implications for Cardiovascular Disease Prevention: A Scientific Statement From the American Heart Association

Abstract: Eating patterns are increasingly varied. Typical breakfast, lunch, and dinner meals are difficult to distinguish because skipping meals and snacking have become more prevalent. Such eating styles can have various effects on cardiometabolic health markers, namely obesity, lipid profile, insulin resistance, and blood pressure. In this statement, we review the cardiometabolic health effects of specific eating patterns: skipping breakfast, intermittent fasting, meal frequency (number of daily eating occasions), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
474
3
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 549 publications
(560 citation statements)
references
References 137 publications
19
474
3
21
Order By: Relevance
“…In contrast, early sleep timing students reported a higher likelihood of eating food in this low-energy-dense, nutrient-rich group between 8:00 and 9:00, suggesting a healthier dietary profile. 4143 Also, group differences in 24-hour eating patterns were only observed for carbohydrates and proteins and not for fruits and vegetables. These results are similar to those of Fleig and Randler, 16 who did not show sleep timing group differences in vegetable and fruit consumption; however, data from another study suggest the contrary, as youth with later sleep timing showed decreased consumption of fruits and vegetables.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, early sleep timing students reported a higher likelihood of eating food in this low-energy-dense, nutrient-rich group between 8:00 and 9:00, suggesting a healthier dietary profile. 4143 Also, group differences in 24-hour eating patterns were only observed for carbohydrates and proteins and not for fruits and vegetables. These results are similar to those of Fleig and Randler, 16 who did not show sleep timing group differences in vegetable and fruit consumption; however, data from another study suggest the contrary, as youth with later sleep timing showed decreased consumption of fruits and vegetables.…”
Section: Discussionmentioning
confidence: 93%
“…Whether dietary strategies can prevent or even reverse cardiometabolic disease has profound implications for public health. In particular, strategies that emphasize fasting, or various regimens of abstinence from food, have emerged as a way to prevent or even reverse cardiometabolic disease (39, 72, 119, 205). …”
Section: Introductionmentioning
confidence: 99%
“…[122][123][124][125] Furthermore, it has been suggested that increased meal frequency may increase postprandial glucose, insulin, IR and blood lipids and may have a negative impact on the fatty acid composition of serum phospholipids. [126][127][128][129] In contrast, others propose that increased meal frequency may exert a beneficial effect on body weight and indices of glycemic control, which may be attributed to nutrient load spreading, producing lower postprandial insulin concentrations, hunger reduction, inhibitory effects of free fatty acids on glucose uptake suppression and increased glucose clearance from the circulation with a significant economy in insulin secretion. 130,131 In a 24-week crossover RCT, our group reported a beneficial effect of a six-meal pattern, without energy restriction, on amelioration of post-oral glucose tolerance test (OGTT) insulin sensitivity and reduction in subjective hunger in lean and obese women with PCOS compared to a three-meal pattern.…”
Section: Pufa and Pcosmentioning
confidence: 99%
“…136 The American Heart Association in their recent scientific statement concluded that meal frequency and timing may be important parameters in the nutrition management of chronic diseases, leading to healthier lifestyle and reduction in cardiometabolic risk factors. 128 …”
Section: Meal Frequency Meal Timing and Pcosmentioning
confidence: 99%